Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward & Peppard (Studi Kasus CV. Merta Bakti) - Yusuf Nur Arifin; Chris Rudianto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
CV. Merta Bakti is a business entity in the form of a building material trading company with the main consumers being the general public. Problems that occur in the CV. Merta Bakti There are two, The first is the availability of data collection of goods that do not match the number of goods in the store. The second problem is that current transactions still use note books and recap sales data every day by hand, this causes work to be longer and ineffective. To overcome the problems that occur, it is necessary to have Information Technology. Information technology that requires strategic planning to be able to support the business running in the CV becomes more efficient and able to compete with competitors. This study uses an approach with the ward & peppard method. In the ward & peppard method there are PESTEL analysis, Value Chain, SWOT, CSF, application mapping using McFarlan Grid, and SI analysis to provide Information System recommendations. The results of the research conducted are IS/IT strategic planning and IS/IT framework which will later be used as a reference for developing IS/IT CV. Merta Bakti in the future.